Neoliberalism and its impact on Latin American crime control fields. (November 2019) - Iturralde, Manuel
In recent years, there has been a growing debate on how, and whether, during the past three decades, a neoliberal penal State, with close ties to the new economic order, has emerged in the United States and in other nations of the Global North. This article seeks to analyse, based on the criticisms that the neoliberal penal State theory has been subject to, whether, and to what extent, such a take on neoliberalism and the penal State may contribute to attaining a plausible explanation of Latin American crime control fields.